2009
DOI: 10.1073/pnas.0906414106
|View full text |Cite
|
Sign up to set email alerts
|

MEIG1 is essential for spermiogenesis in mice

Abstract: Spermatogenesis can be divided into three stages: spermatogonial mitosis, meiosis of spermatocytes, and spermiogenesis. During spermiogenesis, spermatids undergo dramatic morphological changes including formation of a flagellum and chromosomal packaging and condensation of the nucleus into the sperm head. The genes regulating the latter processes are largely unknown. We previously discovered that a bi-functional gene, Spag16, is essential for spermatogenesis. SPAG16S, the 35 kDa, testis-specific isoform derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 39 publications
4
98
0
Order By: Relevance
“…The stage of elongation and condensation of spermatogenesis was shown to be significantly impaired. 11 Salzberg et al 12 obtained similar results showing that developing germ cells rarely differentiated past the spermatogenesis stage in their Meig1 À/ À male mice; the few sperms that managed to reach the epididymis were totally immotile. These consistent findings indicated that the murine Meig1 gene was crucial for spermatogenesis in mice.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The stage of elongation and condensation of spermatogenesis was shown to be significantly impaired. 11 Salzberg et al 12 obtained similar results showing that developing germ cells rarely differentiated past the spermatogenesis stage in their Meig1 À/ À male mice; the few sperms that managed to reach the epididymis were totally immotile. These consistent findings indicated that the murine Meig1 gene was crucial for spermatogenesis in mice.…”
Section: Introductionsupporting
confidence: 62%
“…11,12 Meig1 is a murine gene with testis-specific expression. Zhang et al 11 found that homozygous Meig1-knockout male mice are viable but sterile, whereas no obvious defect was detected in heterozygous Meig1-knockout mice. The stage of elongation and condensation of spermatogenesis was shown to be significantly impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Several mouse models, and microscopic studies, strongly suggest that these structures are integral to the formation of normal sperm head shape. [99][100][101] Data also suggest that the manchette is involved in the transport of proteins required for sperm tail formation in a process known as intramanchette transport. [100][101][102] Mouse models have also been critically important in defining the mechanisms of sperm tail formation and have revealed some surprising phenomena and the etiology of several significant human pathologies.…”
Section: Postmeiotic or Spermiogenesis Defectsmentioning
confidence: 99%
“…[99][100][101] Data also suggest that the manchette is involved in the transport of proteins required for sperm tail formation in a process known as intramanchette transport. [100][101][102] Mouse models have also been critically important in defining the mechanisms of sperm tail formation and have revealed some surprising phenomena and the etiology of several significant human pathologies. 52 During the last few years in particular, research has begun to illustrate the importance of axoneme function, not only for sperm motility but also for cilia function in a range of somatic tissues and many aspects of human health.…”
Section: Postmeiotic or Spermiogenesis Defectsmentioning
confidence: 99%
“…In mice, PACRG is associated with MEIG1, which was identified as a binding partner of a CP protein SPAG16 (PF20) [175]. MEIG1-knockout mice show male infertility, but no other phenotypes for ciliopathy are observed [176][177][178]. Further studies suggest that MEIG1/PACRG plays a critical role in the control of the structure called ''manchette'' [179], a microtubule-based structure transiently formed during spermiogenesis.…”
Section: Manchette-dependent Flagellar Formationmentioning
confidence: 99%